Method for controlling abnormal growth of GH4738 high-temperature alloy grains through solid solution and rolling processes
By optimizing the solid solution and rolling process, the abnormal growth of GH4738 high-temperature alloy grains are controlled to obtain fine and uniform grain structure, which solves the problem of abnormal growth of GH4738 high-temperature alloy grains during heat treatment and hot processing, and improves the structural uniformity and mechanical properties of the alloy.
Patent Information
- Application Number
- CN202510540407.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-18
AI Technical Summary
GH4738 high-temperature alloys are prone to abnormal growth of grains during heat treatment and thermal processing, which affects the uniformity of tissue performance, and is difficult to effectively control the existing technology.
Through triple smelting, cutting + solid solution, observation of the grain structure of the sample at one time, statistics of the particle size of the γ' precipitated phase, preparation and labeling of wedge-shaped samples, multi-pass hot rolling, and secondary observation of the grain structure of the sample, the solid solution temperature and rolling temperature are optimized, and abnormal growth of the grain is controlled.
A fine and uniform grain structure is obtained, which significantly improves the structural uniformity and mechanical properties of the alloy, and is suitable for large-scale industrial production.
Smart Images

Figure CN120330630A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat treatment and hot working of superalloy materials, and particularly to a method for controlling abnormal grain growth of GH4738 superalloy by solution treatment and rolling process. Background Technique
[0002] GH4738 superalloy is a precipitation-strengthened nickel-based superalloy. Due to its advantages such as good strength-ductility matching, low crack propagation rate, strong resistance to creep-fatigue interaction, and stable high-temperature microstructure properties, it is widely used in fields such as aerospace, petrochemical, and energy and power. However, due to the high degree of alloying, large deformation resistance, and narrow hot working window in GH4738 superalloy, the phenomena of mixed grains or abnormal grain growth are likely to occur during heat treatment and hot working, seriously affecting the uniformity of the microstructure properties of alloy components. Therefore, how to effectively control the abnormal grain growth of GH4738 superalloy is an urgent problem to be solved.
[0003] Chinese Patent CN113560481A discloses a hot working process of GH4738 nickel-based superalloy. In this process, an ingot is prepared by double melting, and after homogenization treatment, a forging is obtained by forging. Finally, through solution treatment, stabilization treatment, and secondary aging treatment, a forging with relatively uniform grain distribution is obtained. Obviously, the final material prepared is not a hot-rolled material. The cooling method of solution treatment uses water cooling, which makes the cooling rate relatively fast. Although it can prevent the grain size from growing in time, the stabilization treatment and secondary aging treatment will both cause the grain size to grow further, resulting in high cost and low production efficiency.
[0004] Chinese Patent CN103341586A discloses a method for forming a GH4738 nickel-based superalloy turbine disk. This method uses a hard sleeve + thermal insulation cotton composite thermal insulation method, two-pass heating, upsetting and die forging forming, and solution treatment and double aging treatment at a sub-solution temperature to prepare the turbine disk. The heat treatment process is complex, with large operation difficulty and long process flow. It does not perform multi-pass hot rolling but instead performs upsetting and die forging forming. Although the grain size of the prepared material is relatively uniform and the grain boundary carbides are intermittently distributed, mixed grains appear.
[0005] Chinese Patent CN105195541A discloses a method for preparing a fine-grained billet of GH4738 alloy for supercritical power plant steam turbine blades. Although this method can utilize the triaxial compressive stress state of extrusion deformation to improve the plasticity of the ingot, enabling it to exhibit the maximum plastic deformation, and can refine the grains by deformation with a large extrusion ratio; however, not only is the extrusion speed of hot extrusion average, but also machining is required to remove the jacket after extrusion, and the process has a greater impact on the surface quality of the prepared material. Moreover, as the heating temperature of the prefabricated extrusion billet increases, the grain size will grow to 100 μm; while if the heating temperature is reduced, the extrusion pressure will increase significantly, reducing plasticity and increasing the risk of cracking, resulting in defects in the structure and properties, increasing the difficulty of deformation, and reducing the surface quality. Summary of the Invention
[0006] The object of the present invention is to provide a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling processes. By optimizing the solution temperature, rolling temperature and deformation amount, the phenomenon of abnormal grain growth is controlled, and a fine and uniform grain structure is obtained, thereby improving the structural uniformity of the material and enhancing the mechanical properties of the alloy, providing an important theoretical basis and technical support for the actual production and application of GH4738 superalloy.
[0007] In order to obtain the above-mentioned method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling processes, the method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling processes includes the following steps:
[0008] S1. Triple melting: The raw materials of GH4738 superalloy are smelted by a triple process of vacuum induction melting, electroslag remelting and vacuum consumable remelting, and after high-temperature homogenization treatment and cogging forging, GH4738 superalloy bars are prepared.
[0009] S2. Cutting + solution: A wire electrical discharge machine is used to cut heat treatment specimens at the R / 2 of the GH4738 superalloy bars in S1, and solution treatment is carried out at multiple solution temperatures, and after heat preservation, air cooling is carried out to room temperature to obtain multiple solution-treated specimens.
[0010] S3. Observe the grain structure of the specimens for the first time: The multiple solution-treated specimens in S2 are mechanically ground and polished, and the specimens are etched with a solution to observe and obtain the grain structure data of the multiple solution-treated specimens.
[0011] S4. Statistically analyze the particle size of γ' precipitates: The multiple solution-treated specimens in S2 are electrochemically polished, and then electrochemically etched, the γ' phase at different solution temperatures is observed, and an image analysis software is used to statistically analyze the particle size of γ' precipitates in multiple different fields of view of the specimens.
[0012] S5. Preparation and Marking of Wedge Specimens: Multiple solution-treated specimens from S2 are machined into wedge specimens respectively, and the surfaces of the wedge specimens are marked to mark multiple parts with different deformation amounts, obtaining multiple marked wedge specimens;
[0013] S6. Pretreatment before Hot Rolling: First, a layer of high-temperature antioxidant coating is evenly brushed on the surfaces of multiple marked wedge specimens from S5. After the coating dries, a layer of thermal insulation cotton is wrapped around them, obtaining multiple treated wedge specimens;
[0014] S7. Multi-pass Hot Rolling: Multiple treated wedge specimens from S6 are placed in a heat treatment furnace and heated according to the rolling heating regime, and the wedge specimens are subjected to multi-pass hot rolling on a 550 mm hot rolling experimental machine, obtaining multiple hot-rolled wedge specimens;
[0015] S8. Observation of the Grain Structure of Secondary Specimens: Multiple hot-rolled wedge specimens from S7 are mechanically ground and polished, the specimens are etched with a solution, and the grain structure data of multiple hot-rolled wedge specimens are obtained by observation;
[0016] S9. Hardness Measurement: The hardness of multiple hot-rolled wedge specimens from S7 is measured to obtain the corresponding hardness data.
[0017] Optionally, the multiple solution temperatures in S2 are 1030 °C, 1080 °C, and 1120 °C respectively. After holding for 4 h, they are air-cooled to room temperature.
[0018] Optionally, in S3, the specimens are etched with a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH, and the grain structure data of multiple solution-treated specimens are obtained by observation using a ZEISS Axio Scope.A1 optical microscope.
[0019] Optionally, in S4, the electrolytic polishing uses an electrolyte of 20% H2SO4 + 80% CH3OH, the electrolytic etching uses a mixed solution of 150 mL H3PO4 + 10 mL H2SO4 + 15 g CrO3, the γ' phase at different solution temperatures is observed using a TESCAN MIRA4 field emission scanning electron microscope, the image analysis software is Image-Pro Plus image analysis software, and the multiple different fields of view are 5 different fields of view.
[0020] Optionally, the size of the wedge specimens in S5 is 105×30×50 mm 3 and the multiple parts with different deformation amounts are marked as the parts with 10%, 20%, 30%, and 40% deformation.
[0021] Optionally, the component of the high-temperature antioxidant coating in S6 is selected as SiO2 or Al2O3, and the layer thickness is 1 - 2 mm; the layer thickness of the thermal insulation cotton is 10 - 20 mm.
[0022] Optionally, according to the on-site rolling schedule in S7, the rolling temperatures are set to 1020 °C, 1040 °C, 1060 °C, and 1080 °C respectively, the rolling speed is 12 m / min, and four passes of rolling are carried out through 50→42→36→32→30 mm, with a total reduction of 20 mm.
[0023] Optionally, in S8, the solution corrosion uses a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimens, and the grain structure data of multiple solution-treated specimens are obtained by observing with a ZEISS Axio Scope.A1 optical microscope.
[0024] Optionally, in S9, the hardness measurement is to determine the Rockwell hardness of the specimens through a WHR-80D full Rockwell hardness tester, with a loading load of 150 Kg, a loading time of 5 s, 5 points measured for each specimen, and the average value taken.
[0025] Optionally, the chemical composition mass percentages of the GH4738 superalloy are as follows: C 0.02 - 0.08%, Mn ≤ 0.01%, Si ≤ 0.15%, P ≤ 0.015%, S ≤ 0.015%, Cr 18.00 - 21.00%, Co 12.00 - 15.00%, Mo 3.50 - 5.00%, Ti 2.75 - 3.25%, Al 1.20 - 1.60%, B 0.003 - 0.010%, Zr 0.02 - 0.12%, Fe ≤ 2.00%, Cu ≤ 0.10%, and the balance is Ni and unavoidable impurities.
[0026] The above technical solution has at least the following beneficial effects compared with the prior art:
[0027] In the above solution, the present invention provides a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling processes, which can obtain fine grains through the technological steps of triple melting, cutting + solution treatment, observing the grain structure of specimens once, statistically analyzing the particle size of γ' precipitated phases, preparing and marking wedge-shaped specimens, pre-treatment before hot rolling, multi-pass hot rolling, and observing the grain structure of specimens twice, thereby significantly improving the comprehensive high-temperature performance of the alloy.
[0028] Through triple melting, the prepared GH4738 superalloy bars have high purity and less segregation.
[0029] Through cutting + solution treatment, the distribution of alloying elements is more uniform, segregation is reduced, and the structure is homogenized.
[0030] By observing the grain structure of specimens once, the present invention can obtain the change trend of grain size.
[0031] By statistically analyzing the grain size of the γ' precipitated phase, the present invention can obtain the distribution characteristics of the γ' precipitated phase and its influence law on the microstructure.
[0032] By preparing and marking a wedge-shaped specimen, the present invention can obtain different deformed parts.
[0033] By pre-treating before hot rolling, the present invention enables the wedge-shaped specimen to be oxidation-resistant during heat treatment.
[0034] By multi-pass hot rolling, the present invention enables the wedge-shaped specimen to obtain microstructures with different deformation amounts.
[0035] By observing the grain microstructure of the specimen for the second time, the present invention can obtain a fine and uniform grain microstructure.
[0036] In summary, compared with the traditional powder metallurgy hot isostatic pressing for preparing superalloys that requires removing the cladding, the present invention effectively controls the abnormal grain growth of GH4738 superalloy by optimizing the solution temperature, rolling temperature, and deformation amount, obtains a fine and uniform grain microstructure, significantly improves the microstructure uniformity and mechanical properties of the alloy, and has important guiding significance for controlling the abnormal grain growth during the actual production and application of GH4738 superalloy; this method is simple, easy to operate, environmentally friendly, low-cost, short-process, and high-efficiency, and is conducive to large-scale industrial production and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the following described drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0038] Figure 1 It is the original microstructure diagram of the GH4738 superalloy bar prepared by the method for controlling the abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0039] Figure 2It is the microstructure diagram of the GH4738 superalloy bar after solution treatment in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention; among them, the figure labeled a1 is the grain microstructure diagram at a solution temperature of 1030 °C, the figure labeled a2 is the primary γ′ phase and secondary γ′ phase microstructure diagram at a solution temperature of 1030 °C, the figure labeled b1 is the grain microstructure diagram at a solution temperature of 1080 °C, the figure labeled b2 is the primary γ′ phase and secondary γ′ phase microstructure diagram at a solution temperature of 1080 °C, the figure labeled c1 is the grain microstructure diagram at a solution temperature of 1120 °C, and the figure labeled c2 is the primary γ′ phase and secondary γ′ phase microstructure diagram at a solution temperature of 1120 °C;
[0040] Figure 3 It is the schematic diagram of the shape and size of the wedge-shaped specimen prepared in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0041] Figure 4 It is the process diagram of the rolling heating system in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0042] Figure 5 It is the microstructure diagram of different deformation amount positions of the 1020 °C hot-rolled wedge-shaped specimen in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0043] Figure 6 It is the microstructure diagram of different deformation amount positions of the 1040 °C hot-rolled wedge-shaped specimen in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0044] Figure 7 It is the microstructure diagram of different deformation amount positions of the 1060 °C hot-rolled wedge-shaped specimen in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0045] Figure 8 It is the microstructure diagram of different deformation amount positions of the 1080 °C hot-rolled wedge-shaped specimen in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention;
[0046] Figure 9 It is the hardness distribution diagram of the wedge-shaped specimen at different deformation amount positions in a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process of the present invention. Detailed implementation manners
[0047] The technical solutions in the present invention will be described below with reference to the accompanying drawings.
[0048] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to give examples, illustrations or explanations. Any embodiment or design solution described as an "example" in the present invention should not be construed as being more preferred or having more advantages than other embodiments or design solutions. Specifically, the use of the word "example" is intended to present concepts in a specific manner. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or either of the two can be selected.
[0049] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference is not emphasized, the meanings they express are the same.
[0050] In the embodiments of the present invention, sometimes a subscript such as W1 may be written in a non-subscript form such as W1. When the difference is not emphasized, the meanings they express are the same.
[0051] To make the technical problems to be solved, technical solutions and advantages of the present invention clearer, the following will be described in detail with reference to the drawings and specific embodiments.
[0052] A method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process, the method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process includes the following steps:
[0053] S1. Triple melting: Smelt the raw materials of GH4738 superalloy through the triple process of vacuum induction melting, electroslag remelting and vacuum consumable remelting, and prepare GH4738 superalloy bars through high-temperature homogenization treatment and blooming forging.
[0054] S2. Cutting + solution: Use a wire electrical discharge machine to cut heat treatment specimens at the R / 2 of the GH4738 superalloy bars in S1, and perform solution treatment at multiple solution temperatures respectively. After heat preservation, air-cool to room temperature to obtain multiple solution-treated specimens.
[0055] S3. Observe the grain structure of the specimens for the first time: Mechanically grind and polish the multiple solution-treated specimens in S2, corrode the specimens with a solution, and observe to obtain the grain structure data of the multiple solution-treated specimens.
[0056] S4. Statistically analyze the particle size of γ' precipitates: Electrolytically polish the multiple solution-treated specimens in S2, then perform electrolytic corrosion, observe the γ' phase at different solution temperatures, and use image analysis software to statistically analyze the particle size of γ' precipitates in multiple different fields of view of the specimens.
[0057] S5. Preparation and marking of wedge-shaped specimens: Machine-process the multiple solution-treated specimens in S2 into wedge-shaped specimens respectively, and mark the surfaces of the wedge-shaped specimens, and mark the parts with multiple different deformation amounts respectively to obtain multiple marked wedge-shaped specimens.
[0058] S6. Pre-treatment before hot rolling: First, evenly brush a layer of high-temperature antioxidant coating on the surfaces of multiple marked wedge-shaped specimens in S5. After the coating dries, wrap a layer of heat-insulating cotton to obtain multiple processed wedge-shaped specimens.
[0059] S7. Multi-pass hot rolling: Put multiple processed wedge-shaped specimens in S6 into a heat treatment furnace, heat them according to the rolling heating system, and perform multi-pass hot rolling on the wedge-shaped specimens on a 550 mm hot rolling experimental machine to obtain multiple hot-rolled wedge-shaped specimens.
[0060] S8. Second observation of the grain structure of the specimens: Mechanically grind and polish multiple hot-rolled wedge-shaped specimens in S7, corrode the specimens with a solution, and observe to obtain the grain structure data of multiple hot-rolled wedge-shaped specimens.
[0061] S9. Hardness measurement: Measure the hardness of multiple hot-rolled wedge-shaped specimens in S7 to obtain the corresponding hardness data.
[0062] Particularly, the multiple solution temperatures in S2 are 1030 °C, 1080 °C, and 1120 °C respectively. After holding for 4 h, air-cool to room temperature.
[0063] Particularly, in S3, the solution corrosion uses a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimens. The grain structure data of multiple solution-treated specimens obtained by observation is using a ZEISS Axio Scope.A1 optical microscope.
[0064] Particularly, in S4, the electrolytic polishing uses an electrolyte of 20% H2SO4 + 80% CH3OH, and the electrolytic corrosion uses a mixed solution of 150 mL H3PO4 + 10 mL H2SO4 + 15 g CrO3. The γ' phase at different solution temperatures is observed using a TESCAN MIRA4 field emission scanning electron microscope. The image analysis software is Image-Pro Plus image analysis software, and the multiple different fields of view are 5 different fields of view.
[0065] Particularly, the size of the wedge-shaped specimens in S5 is 105×30×50 mm 3 The parts with multiple different deformation amounts are marked as the parts with 10%, 20%, 30%, and 40% respectively.
[0066] Particularly, the component of the high-temperature antioxidant coating in S6 is selected as SiO2 or Al2O3, the layer thickness is 1 - 2 mm; the layer thickness of the heat-insulating cotton is 10 - 20 mm.
[0067] Specifically, in S7, according to the on-site rolling schedule, the rolling temperatures are set to 1020°C, 1040°C, 1060°C, and 1080°C respectively, the rolling speed is 12 m / min, and four passes of rolling are carried out with dimensions of 50→42→36→32→30 mm, with a total reduction of 20 mm.
[0068] Specifically, in S8, solution corrosion is carried out using a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimens, and the grain structure data of multiple solution-treated specimens are obtained by observing with a ZEISS Axio Scope.A1 optical microscope.
[0069] Specifically, in S9, the hardness measurement is carried out by measuring the Rockwell hardness of the specimens with a WHR-80D full Rockwell hardness tester. The loading load is 150 Kg, the loading time is 5 s, 5 points are measured for each specimen, and the average value is taken.
[0070] Specifically, the chemical composition mass percentages of the GH4738 superalloy are as follows: C 0.02 - 0.08%, Mn ≤ 0.01%, Si ≤ 0.15%, P ≤ 0.015%, S ≤ 0.015%, Cr 18.00 - 21.00%, Co 12.00 - 15.00%, Mo 3.50 - 5.00%, Ti 2.75 - 3.25%, Al 1.20 - 1.60%, B 0.003 - 0.010%, Zr 0.02 - 0.12%, Fe ≤ 2.00%, Cu ≤ 0.10%, and the balance is Ni and unavoidable impurities.
[0071] In the following Examples 1 to 4, the chemical composition mass percentages of the GH4738 superalloy are: C 0.02 - 0.08%, Mn ≤ 0.01%, Si ≤ 0.15%, P ≤ 0.015%, S ≤ 0.015%, Cr 18.00 - 21.00%, Co 12.00 - 15.00%, Mo 3.50 - 5.00%, Ti 2.75 - 3.25%, Al 1.20 - 1.60%, B 0.003 - 0.010%, Zr 0.02 - 0.12%, Fe ≤ 2.00%, Cu ≤ 0.10%, and the balance is Ni and unavoidable impurities.
[0072] The method for controlling abnormal grain growth of GH4738 superalloy by specific solution and rolling processes is as follows:
[0073] S1. Triple melting: The raw materials of the GH4738 superalloy are smelted by a triple process of vacuum induction melting, electroslag remelting, and vacuum consumable remelting, and after high-temperature homogenization treatment and blooming forging, GH4738 superalloy bars are prepared. Figure 1The original microstructure of the alloy bar is shown, which is mainly composed of equiaxed austenite grains, annealing twins and a small amount of carbides, and the average grain size is 54.3μm.
[0074] S2, Cutting + Solution treatment: Use a wire electrical discharge machine to cut heat treatment specimens at the R / 2 position of the GH4738 superalloy bar in S1, and perform solution treatment at 1030°C, 1080°C, and 1120°C respectively. After holding for 4h, air cool to obtain multiple solution-treated specimens;
[0075] S3, Observe the grain structure of the specimens for the first time: Mechanically grind and polish the multiple solution-treated specimens in S2, etch the specimens with a solution of 1.5g CuSO4 + 40mL HCl + 20mL C2H5OH, and use a ZEISS Axio Scope.A1 optical microscope to observe the grain structure of the specimens to obtain the grain structure data of multiple solution-treated specimens;
[0076] S4, Statistically analyze the particle size of γ' precipitates: Electrolytically polish the multiple solution-treated specimens in S2 with an electrolyte of 20%H2SO4 + 80% CH3OH, then perform electrolytic etching with a mixed solution of 150mL H3PO4 + 10mL H2SO4 + 15g CrO3, observe the γ' phase at different solution temperatures with a TESCAN MIRA4 field emission scanning electron microscope, and use Image-Pro Plus image analysis software to statistically analyze the particle size of γ' precipitates in 5 different fields of view of the specimens. The obtained initial grain sizes are 41.8μm, 286.0μm, and 465.1μm respectively, and the corresponding primary γ′ phase particle size is about 250nm, and the secondary γ′ phase particle size is about 70nm, as Figure 2 shown.
[0077] S5, Preparation and marking of wedge-shaped specimens: Machine the multiple solution-treated specimens in S2 into wedge-shaped specimens with the dimensions as Figure 3 shown, and mark lines on the surface of the wedge-shaped specimens, and mark the parts with deformation amounts of 10%, 20%, 30%, and 40% respectively.
[0078] S6, Pretreatment before hot rolling: First, evenly brush a layer of high-temperature antioxidant coating on the surface of the multiple marked wedge-shaped specimens in S5. After the coating dries, wrap a layer of heat-insulating cotton to obtain multiple processed wedge-shaped specimens.
[0079] The subsequent S7 - S9 are specifically described in Examples 1 - 4.
[0080] Example 1
[0081] The S7 - S9 of this example are as follows:
[0082] S7. Multi-pass hot rolling: Put multiple processed wedge-shaped specimens of S6 into a heat treatment furnace, heat them according to the rolling heating system, and perform multi-pass hot rolling on the wedge-shaped specimens on a 550 mm hot rolling experimental machine. The rolling temperature is 1020 °C, the rolling speed is 12 m / min, and four passes of rolling are carried out through 50→42→36→32→30 mm, with a total reduction of 20 mm; multiple hot-rolled wedge-shaped specimens are obtained;
[0083] S8. Second observation of the grain structure of the specimen: Air-cool multiple hot-rolled wedge-shaped specimens of S7 to room temperature, cut the rolled wedge-shaped specimens along the marked line, after mechanical grinding and polishing, use a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimen, and use a ZEISS Axio Scope.A1 optical microscope to observe the grain structure of the specimen; Figure 5 The structure at different deformation positions of the wedge-shaped specimen hot-rolled at 1020 °C after heat treatment at different solution temperatures;
[0084] S9. Hardness measurement: Measure the Rockwell hardness of multiple hot-rolled wedge-shaped specimens of S7 through a WHR-80D full Rockwell hardness tester. The loading load is 150 Kg, the loading time is 5 s, 5 points are measured for each specimen, and the average value is taken to obtain the surface hardness as shown in Table 1.
[0085] Table 1 Hardness (HRC) after hot rolling at 1020 °C
[0086]
[0087]
[0088] Example 2
[0089] The S7-S9 of this example are as follows:
[0090] S7. Multi-pass hot rolling: Put multiple processed wedge-shaped specimens of S6 into a heat treatment furnace, heat them according to the rolling heating system, and perform multi-pass hot rolling on the wedge-shaped specimens on a 550 mm hot rolling experimental machine. The rolling temperature is 1040 °C, the rolling speed is 12 m / min, and four passes of rolling are carried out through 50→42→36→32→30 mm, with a total reduction of 20 mm; multiple hot-rolled wedge-shaped specimens are obtained;
[0091] S8. Second observation of the grain structure of the specimen: Air-cool multiple hot-rolled wedge-shaped specimens of S7 to room temperature, cut the rolled wedge-shaped specimens along the marked line, after mechanical grinding and polishing, use a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimen, and use a ZEISS Axio Scope.A1 optical microscope to observe the grain structure of the specimen; Figure 6Microstructures at different deformation positions of the wedge-shaped specimens after heat treatment at different solution temperatures and hot-rolled at 1040°C
[0092] S9. Hardness measurement: The Rockwell hardness of multiple hot-rolled wedge-shaped specimens of S7 was measured by a WHR-80D full Rockwell hardness tester. The loading load was 150 Kg, the loading time was 5 s, 5 points were measured for each specimen, and the average value was taken to obtain the surface hardness as shown in Table 2.
[0093] Table 2 Hardness (HRC) after hot rolling at 1040°C
[0094]
[0095] Example 3
[0096] S7 - S9 of this example are as follows:
[0097] S7. Multi-pass hot rolling: Multiple processed wedge-shaped specimens of S6 were placed in a heat treatment furnace, heated according to the rolling heating system, and multi-pass hot rolling was carried out on the wedge-shaped specimens on a 550 mm hot rolling experimental machine. The rolling temperature was 1060°C, the rolling speed was 12 m / min, and four passes of rolling were carried out: 50 → 42 → 36 → 32 → 30 mm, with a total reduction of 20 mm; multiple hot-rolled wedge-shaped specimens were obtained.
[0098] S8. Secondary observation of the grain microstructure of the specimens: Multiple hot-rolled wedge-shaped specimens of S7 were air-cooled to room temperature, cut along the marked line, mechanically ground and polished, and then the specimens were corroded with a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH, and the grain microstructure of the specimens was observed using a ZEISS Axio Scope.A1 optical microscope. Figure 7 Microstructures at different deformation positions of the wedge-shaped specimens after heat treatment at different solution temperatures and hot-rolled at 1060°C
[0099] S9. Hardness measurement: The Rockwell hardness of multiple hot-rolled wedge-shaped specimens of S7 was measured by a WHR-80D full Rockwell hardness tester. The loading load was 150 Kg, the loading time was 5 s, 5 points were measured for each specimen, and the average value was taken to obtain the surface hardness as shown in Table 3.
[0100] Table 3 Hardness (HRC) after hot rolling at 1060°C
[0101]
[0102] Example 4
[0103] S7 - S9 of this example are as follows:
[0104] S7, multi-pass hot rolling: put the multiple processed wedge-shaped samples of S6 into a heat treatment furnace, heat them according to the rolling heating system, and perform multi-pass hot rolling on the wedge-shaped samples on a 550mm hot rolling test machine, with a rolling temperature of 1080°C, a rolling speed of 12m / min, and four passes of 50→42→36→32→30mm, with a total reduction of 20mm; obtain multiple hot-rolled wedge-shaped samples;
[0105] S8. Secondary observation of the grain structure of the sample: air-cool the multiple hot-rolled wedge-shaped samples of S7 to room temperature, cut the rolled wedge-shaped samples along the marking line, and after mechanical grinding and polishing, use 1.5g CuSO4+40mL HCl+20mL C2H5OH solution to corrode the sample, and use ZEISS Axio Scope.A1 optical microscope to observe the grain structure of the sample; Figure 8 The microstructures of wedge-shaped specimens at different deformation positions after heat treatment at different solution temperatures and hot rolling at 1080℃;
[0106] S9. Hardness measurement: The Rockwell hardness of multiple hot-rolled wedge specimens of S7 was measured by a WHR-80D full Rockwell hardness tester. The loading load was 150 kg and the loading time was 5 s. Five points were measured for each specimen and the average value was taken to obtain the surface hardness as shown in Table 4.
[0107] Table 4 Hardness after hot rolling at 1080℃ (HRC)
[0108]
[0109] From Examples 1 to 3 corresponding Figures 5 to 7 It can be seen that the wedge-shaped specimens after solution treatment at 1030℃ were hot rolled at different temperatures and deformations, and their structures were relatively fine and uniform, without abnormal grain growth; while the wedge-shaped specimens after solution treatment at 1080℃ and 1120℃ were hot rolled at different temperatures and deformations, and abnormal grain growth (AGG) occurred at deformations of 10% and 20%. With the increase of deformation (30%→40%), the original grains were deformed, and the grains were gradually elongated and refined along the extension direction of the wedge-shaped specimens.
[0110] From Example 4 Figure 8 It can be seen that the original grains are broken, and the small dynamically recrystallized grains nucleate at the original grain boundaries and twin boundaries and gradually grow to form a necklace structure. As the deformation increases from 10% to 40%, the volume fraction of dynamic recrystallization gradually increases. However, the necklace structure is a mixed crystal structure with large structural inhomogeneity, which is not conducive to the mechanical properties of the alloy. Therefore, hot rolling at 1080℃ should be avoided.
[0111] The hardness distributions of the wedge-shaped specimens corresponding to the above Examples 1 to 4 at different deformation positions are as follows Figure 9 shown. It can be seen from the figure that when the solution temperature is constant, as the rolling deformation increases from 10% to 40%, the hardness of the alloy gradually increases.
[0112] In the above solution, the present invention provides a method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling processes, which can obtain fine grains through the technological steps of triple melting, cutting + solution, observing the grain structure of the specimen once, counting the particle size of γ' precipitated phases, preparing and marking wedge-shaped specimens, pre-treatment before hot rolling, multi-pass hot rolling, and observing the grain structure of the specimen twice, so that the comprehensive high-temperature properties of the alloy are significantly improved.
[0113] Through triple melting, the present invention makes the prepared GH4738 superalloy bar have high purity and less segregation.
[0114] Through cutting + solution, the present invention makes the distribution of alloying elements more uniform, reduces segregation, and homogenizes the structure.
[0115] Through observing the grain structure of the specimen once, the present invention can obtain the change trend of the grain size.
[0116] Through counting the particle size of γ' precipitated phases, the present invention can obtain the distribution characteristics of γ' precipitated phases and the influence law on the structure.
[0117] Through the preparation and marking of wedge-shaped specimens, the present invention can obtain different deformation positions.
[0118] Through pre-treatment before hot rolling, the present invention makes the wedge-shaped specimen antioxidant during heat treatment.
[0119] Through multi-pass hot rolling, the present invention makes the wedge-shaped specimen obtain structures with different deformations.
[0120] Through observing the grain structure of the specimen twice, the present invention can obtain fine and uniform grain structures.
[0121] In summary, compared with the traditional powder metallurgy hot isostatic pressing for preparing superalloys that requires removing the cladding, the present invention effectively controls the abnormal grain growth of GH4738 superalloy by optimizing the solution temperature, rolling temperature, and deformation amount, obtains fine and uniform grain structures, significantly improves the structure uniformity and mechanical properties of the alloy, and has important guiding significance for controlling abnormal grain growth in the actual production and application process of GH4738 superalloy; this method is simple and easy to operate, environmentally friendly, low-cost, short-process, and high-efficiency, which is conducive to large-scale industrial production and promotion.
[0122] It should be understood that the term "and / or" in this text is merely a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. Here, A and B can be singular or plural. Additionally, the character " / " in this text generally represents an "or" relationship between the associated objects before and after, but it may also represent an "and / or" relationship, and the specific meaning can be understood by referring to the context before and after.
[0123] In the present invention, "at least one" means one or more, and "a plurality" means two or more. "At least one of the following" or its similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, at least one of a, b, or c can represent: a, b, c, a - b, a - c, b - c, or a - b - c, where a, b, and c can be single or multiple.
[0124] It should be understood that in various embodiments of the present invention, the magnitude of the sequence numbers of the above processes does not mean the sequence of execution. The execution sequence of each process should be determined by its function and internal logic, and should not constitute any limitation to the implementation process of the embodiments of the present invention.
[0125] As described above, the above are only specific implementation manners of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention can easily think of changes or substitutions, which should all be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.
Claims
1. A method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process, characterized in that, The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process comprises the following steps: S1. Triple melting: The raw materials of GH4738 superalloy are smelted by a triple process of vacuum induction melting, electroslag remelting and vacuum consumable remelting, and after high-temperature homogenization treatment and cogging forging, GH4738 superalloy bars are prepared. S2. Cutting + solution treatment: A wire electrical discharge cutting machine is used to cut heat treatment specimens at the R / 2 position of the GH4738 superalloy bars in S1, and solution treatment is carried out at multiple solution temperatures, followed by air cooling to room temperature after holding, to obtain multiple solution-treated specimens. S3. Observe the grain structure of the specimens for the first time: The multiple solution-treated specimens in S2 are mechanically ground and polished, and the specimens are etched with a solution to observe and obtain the grain structure data of the multiple solution-treated specimens. S4. Statistic the particle size of γ' precipitates: The multiple solution-treated specimens in S2 are electrochemically polished and then electrochemically etched, the γ' phase at different solution temperatures is observed, and an image analysis software is used to statistic the particle size of γ' precipitates in multiple different fields of view of the specimens. S5. Preparation and marking of wedge-shaped specimens: The multiple solution-treated specimens in S2 are respectively machined into wedge-shaped specimens, and markings are made on the surfaces of the wedge-shaped specimens, and parts with multiple different deformation amounts are marked respectively to obtain multiple marked wedge-shaped specimens. S6. Pretreatment before hot rolling: First, a layer of high-temperature antioxidant coating is evenly brushed on the surfaces of the multiple marked wedge-shaped specimens in S5, and after the coating dries, a layer of heat-insulating cotton is wrapped to obtain multiple treated wedge-shaped specimens. S7. Multi-pass hot rolling: The multiple treated wedge-shaped specimens in S6 are put into a heat treatment furnace, heated according to the rolling heating system, and multi-pass hot rolling is carried out on the wedge-shaped specimens on a 550 mm hot rolling experimental machine to obtain multiple hot-rolled wedge-shaped specimens. S8. Observe the grain structure of the specimens for the second time: The multiple hot-rolled wedge-shaped specimens in S7 are mechanically ground and polished, and the specimens are etched with a solution to observe and obtain the grain structure data of the multiple hot-rolled wedge-shaped specimens. S9. Hardness measurement: Hardness measurement is carried out on the multiple hot-rolled wedge-shaped specimens in S7 to obtain the corresponding hardness data.
2. The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process according to claim 1, characterized in that, The multiple solution temperatures in S2 are 1030 °C, 1080 °C and 1120 °C respectively, and after holding for 4 h, they are air cooled to room temperature.
3. The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process according to claim 1, characterized in that, In S3, the solution etching uses a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to etch the specimens, and the grain structure data of the multiple solution-treated specimens are observed and obtained by using a ZEISS Axio Scope.A1 optical microscope.
4. The method for controlling abnormal grain growth of GH4738 superalloy by solution treatment and rolling process according to claim 1, characterized in that In S4, the electrochemical polishing uses an electrolyte of 20% H2SO4 + 80% CH3OH, the electrochemical etching uses a mixed solution of 150 mL H3PO4 + 10 mL H2SO4 + 15 g CrO3, the γ' phase at different solution temperatures is observed by using a TESCAN MIRA4 field emission scanning electron microscope, the image analysis software is Image-Pro Plus image analysis software, and the multiple different fields of view are 5 different fields of view.
5. The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process according to claim 1, characterized in that, The dimensions of the wedge-shaped specimen in S5 are 105×30×50 mm 3 , and the parts with multiple different deformation amounts are respectively marked as the parts with 10%, 20%, 30% and 40%.
6. The method for controlling abnormal grain growth of GH4738 superalloy by solution treatment and rolling process according to claim 1, wherein The component selection of the medium and high temperature oxidation resistant coating in S6 is SiO2 or Al2O3, and the layer thickness is 1 - 2 mm; the layer thickness of the thermal insulation cotton is 10 - 20 mm.
7. The method for controlling abnormal grain growth of GH4738 superalloy by solution treatment and rolling process according to claim 1, characterized in that, In S7, according to the on-site rolling schedule, the rolling temperatures are set at 1020°C, 1040°C, 1060°C, and 1080°C respectively, the rolling speed is 12 m / min, and it undergoes four passes of rolling of 50→42→36→32→30 mm, with a total reduction of 20 mm.
8. The method for controlling abnormal grain growth of GH4738 superalloy by solution treatment and rolling process according to claim 1, characterized in that In S8, the solution corrosion uses a solution of 1.5 g CuSO4 + 40 mL HCl + 20 mL C2H5OH to corrode the specimens, and the grain structure data of multiple solution-treated specimens are obtained by observing with a ZEISS Axio Scope.A1 optical microscope.
9. The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process according to claim 1, characterized in that, In S9, the hardness measurement is carried out by using a WHR-80D full Rockwell hardness tester to measure the Rockwell hardness of the specimens, with a loading load of 150 Kg, a loading time of 5 s, measuring 5 points for each specimen, and taking the average value.
10. The method for controlling abnormal grain growth of GH4738 superalloy by solution and rolling process according to claim 1, characterized in that, The chemical composition mass percentages of the GH4738 superalloy are as follows: C 0.02 - 0.08%, Mn ≤ 0.01%, Si ≤ 0.15%, P ≤ 0.015%, S ≤ 0.015%, Cr 18.00 - 21.00%, Co 12.00 - 15.00%, Mo 3.50 - 5.00%, Ti 2.75 - 3.25%, Al 1.20 - 1.60%, B 0.003 - 0.010%, Zr 0.02 - 0.12%, Fe ≤ 2.00%, Cu ≤ 0.10%, and the balance is Ni and unavoidable impurities.
Citation Information
Patent Citations
Method for achieving forming of GH4738 nickel-base superalloy turbine discs
CN103341586A
GH4738 alloy fine-grain blank manufacturing method for supercritical power station steam turbine blade
CN105195541A
Hot working process of GH4738 nickel-based superalloy
CN113560481A